1984
DOI: 10.1063/1.333095
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of bonding-solder deterioration observed in long-lived semiconductor lasers: Solder migration and whisker growth

Abstract: This paper reports on catastrophic degradation, called sudden failure (SF), that is observed in both AlGaAs/GaAs and InGaAsP/InP double-heterostructure lasers. The SF observed here is not associated with electrical surge effects and appears unexpectedly in the middle of a long-term, stable operation. It was found that this type of SF can be caused by aging-induced metallurgical deterioration at the interfacial bonding solder layer. Among the metallurgical deteriorations observed were (1) solder migration into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The growths of Sn and In whiskers have been observed between laser and submount as a result of solder surface migration and electromigration. 2,3 Hard solders, including Au-rich Au-Sn, Au-Si, and Au-Ge alloys, have higher melting temperatures and higher yield strengths. Therefore, they are more resistant to creep.…”
Section: Introductionmentioning
confidence: 99%
“…The growths of Sn and In whiskers have been observed between laser and submount as a result of solder surface migration and electromigration. 2,3 Hard solders, including Au-rich Au-Sn, Au-Si, and Au-Ge alloys, have higher melting temperatures and higher yield strengths. Therefore, they are more resistant to creep.…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional electromigration experiments, In was transported toward the anode side and voids/hillocks nucleated at the cathode/anode, respectively [34,35,39]. In the surface electromigration experiments, it was reported that one mono layer of In moved on the surface toward the cathode while the anode side edge of In stayed when very thin In layer was fabricated on Si surface [36][37][38].…”
Section: Solder Bump Deformationmentioning
confidence: 97%
“…However, this makes soft solder subject to thermal fatigue and creep rupture, causing long-term reliability problems (Solomon, 1986;Lau & Rice, 1985). They are also attributed to solder instabilities like whisker growth, void formation at the bonding part, and diffusion growth (Mizuishi et al, 1983(Mizuishi et al, , 1984Sabbag &McQueen, 1975 and obstruct its optical beam. As mentioned earlier, the laser diode package will experience elevated temperature during operation.…”
Section: Thermal Interface Materialsmentioning
confidence: 99%